The three-way interplay of motor coordination, body fatness and physical activity in adolescents: a preliminary study - Chagas Daniel das Virgens; Batista Luiz Alberto (Sciendo, 2019)
Study aim: The purposes of this study were to analyze: the influence of physical activity level on the association between motor coordination and body fatness; the influence of body fatness on the association between motor coordination and physical activity; and how much physical activity and body fatness, separately and together, explain motor coordination in adolescent boys.